Hand Grip Strength (HGS) in children aged 9-10 years based on nutritional status - Safitri, Oktaria; Widjaja, Nur Aisiyah; Adi, Annis Catur (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Hand grip strength (HGS) is crucial across life stages, reflecting health and function. It influenced by age, gender, and body size. HGS correlates with anthropometric traits like weight and hand dominance. It predicts health outcomes, aids in clinical assessments, and guides early interventions for optimal pediatric health. This study was elaborated to evaluate the HGS difference in children aged 9-10 years based on nutritional status.Methods: A cross-sectional study was conducted involving children aged 9-10 years collected using the consecutive sampling method. Handgrip strength was measured using a digital dynamometer. Subjects were categorized based on weight-for-age z-score (WAZ) and height-for-age z-score (HAZ) into groups representing different nutritional statuses.Results: The study revealed significant differences in muscle mass percentage across nutritional status groups, namely severely-underweight (16.53%), underweight (18.46%), normal-weight (22.14%), and overweight (31.04%) (P